2019
DOI: 10.1002/jmcd.12138
|View full text |Cite
|
Sign up to set email alerts
|

What Do the AMCD Multicultural and Social Justice Counseling Competencies Mean in the Context of Black Lives Matter?

Abstract: In this article, the authors discuss how the legacy of hypersurveillance and egregious anti‐Black vigilante violence and police brutality helped foment the Black Lives Matter movement. The authors consider how the Multicultural and Social Justice Counseling Competencies (Ratts, Singh, Nassar‐McMillan, Butler, & McCullough, 2015) can operate as an ethical professional framework counselor educators can use with counselors‐in‐training to increase their awareness, knowledge, and skills in relation to the state‐san… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 26 publications
0
29
1
Order By: Relevance
“…Specifically, the findings suggest a potential need for training in identifying experiences as UPV and in advocating for client populations that experience UPV. As suggested by Washington and Henfield (2019), counselor educators have an ethical obligation to prepare counselors to address issues of oppression. Thus, findings from this study imply a potential need for counselor educators to emphasize and integrate social justice competence related to UPV into the curriculum and instruction for counselors‐in‐training.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, the findings suggest a potential need for training in identifying experiences as UPV and in advocating for client populations that experience UPV. As suggested by Washington and Henfield (2019), counselor educators have an ethical obligation to prepare counselors to address issues of oppression. Thus, findings from this study imply a potential need for counselor educators to emphasize and integrate social justice competence related to UPV into the curriculum and instruction for counselors‐in‐training.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the importance of preparing counselors to address social justice issues like UPV and other matters of racial injustice, research suggests that gaps exist in counselor training for identifying and treating race‐based trauma (Hemmings & Evans, 2018; Washington & Henfield, 2019). Hemmings and Evans (2018) found that despite 71% of participants having worked with clients who had experienced racism, only 33% reported receiving training to identify race‐based trauma.…”
Section: Upv and The Counseling Professionmentioning
confidence: 99%
“…However, I now understand that the intersections of identities are inextricably linked to all facets of life, including an academic's positionality, research, teaching, and service (Porter et al, 2020). This call for antiracist pedagogy and a critical examination of Black people's experiences is integral to my identity and for many other counselor educators (Haskins & Singh, 2015;Holcomb-McCoy, 2004;Pieterse, 2009;Washington & Henfield, 2019). Across this narrative, I will address the challenges faced when embodying an antiracist standpoint in the areas of positionality and research/teaching.…”
Section: Living and Teaching At The Margins: Reflections Of An Antiracist Counselor Educator (Jab's Narrative)mentioning
confidence: 99%
“…Here is where the formation of the social sciences (e.g., anthropology, psychology, and other helping professions) and their egregious practices have been justifiably implicated and scrutinized for their respective roles in fabricating narratives about the purported pathological proclivities of the cultural "other" under the guise of objective science, to facilitate the making of the modern world as we now know it (Castro-Gómez & Martin, 2002;Goodman et al, 2015;Judy, 1993;Marsella, 2015;Prilleltensky, 1994;Rivera & Fernandez, 2015;Shange, 2019). Stated differently, this "political critical standpoint" to the study of the social sciences recognizes the paramount importance of imbuing preservice helping professionals with "the skills necessary to scrutinize the ideological repercussions of particular forms of theorizing" so that they understand "the need to be educated in the political, social, and moral dimensions of psychology is just as important as being taught how to evaluate the methodology and research design of a study in human behavior" (Prilleltensky, 1994, p. 5;Washington & Henfield, 2019).…”
Section: Addressing Western Hegemony In the Counseling Canon (A R W's Narrative)mentioning
confidence: 99%
See 1 more Smart Citation